A Bibliometric Analysis of Insurtech Indexed by Dimensions AI Using Vosviewer - Muhammad Zulva Zeta Zaidan; Musthafa Arkan; Muhammad Gilang Putra; Yaser Taufik Ramlan; Muhammad Syafi’i Antonio (Indonesian Journal of Banking and Financial Technology, 2023)
The insurance industry, which is increasingly developing with aligned technology, is an opportunity for the public to be able to take advantage of various features that can facilitate public access to insurance. Insurtech is a new feature that aims to make it easier for people to access insurance. The development of insurtech is accompanied by the development of researchers in researching the impact of insurtech on society. This article maps the development of research on insurtech indexed on platform dimensions with the Vosviewer application. The results of this research are that there are 271 scientific journal publications with the theme of insurtech. The majority of the types of publications published are in the form of articles. As well as the hottest topic that is often discussed by researchers is financial technology.